Participación sociocultural en padres de familia en aprendizajes de escolares de 6to. Grado Institución Educativa “Jose Emilio Lefebvre Francoeu”-Moche. - Camones Arana, Evelyn Lorena (2019)
The present Investigation Report was carried out in Moche Pueblo, District of Moche, Province of Trujillo; Its purpose is to explain how the sociocultural participation of parents is expressed or manifested in the school and how this participation contributes to achieving the learning of sixth grade students of the primary level of The Educational Institution José Emilio Lefebvre Francoeur, Distrito of Moche 2018. It has been possible to determine that the social and cultural participation of parents in the educational process of their school children which they consider to be one of the main fac-tors that contribute to the learning achievements of schoolchildren that at the same time positive participation seem to depend on how parents and teachers understand the comple-mentarity of their roles, in terms of a collaboration in which there are certain basic continu-ities between home and school. Likewise social participation we find the interpersonal relationships that students are estab-lishing with their classmates and teachers in which parents consider that good communica-tion with teachers can solve part of the educational problems they face , and see the ab-sence of this as the cause of the problems. The cultural participation is linked to the learning that reaches the sixth grade of primary school, which have been acquired by teachers and parents who are understood to also have the obligation to monitor the situation to demonstrate effectiveness and equity in the results of the learning achievements of their school children.